SUB EPIDURAL HEMATOMA IN STROKE: A RARE BUT CRITICAL CONSIDERATION IN ADULT PATIENTS - Nafisaxon Jabborova Toxirjаnovna (Web of Journals Publishing, 2025)
Sub-epidural hematoma (SEH) is a rare but significant complication in stroke patients. While epidural hematomas are commonly associated with traumatic brain injury, their occurrence in stroke cases presents unique diagnostic and therapeutic challenges. This article explores the pathophysiology, diagnostic methods, and management of SEH in adult stroke patients, providing a comprehensive analysis of recent literature and clinical cases. Understanding the implications of SEH in stroke patients is crucial for timely intervention and improved patient outcomes.
Keywords: Sub-epidural hematoma, stroke, cerebrovascular accident, brain hemorrhage, neuroimaging, neurosurgery, hematoma management.